How Information Technology Affects Decision Making - Tiwow, Gilly Marlya; Rawis, Joulanda A.M.; Tambingon, Henny N.; Kambey, Joseph (JR Education, 2023)
One of the most important contributions of information technologies to the leaders was to enhance the performance level with the help of alternatives provided by information technology. Information technology provided support to the decision-making process. The main important point in the decision-making was giving the most appropriate and best decisions. This research was conducted to analyze the effect of Information technology on Junior high school principals in Tomohon City. The study was conducted with a quantitative approach using a simple regression technique. The result shows that there was a significant impact of Information technology on principal decision-making. Therefore, suggested that education institution leaders enhance the maximization of Information Technology.